A literature review on the parking demand of park and ride facilities - Syed Adnan, Sharifah Adibah Alyia; Kadar Hamsa, Abdul Azeez (2012)
The increasing number of private vehicles in Malaysia has been inducing detrimental effects on the society in terms of increase in traffic congestion, noise and air pollution and accident casualties. Traffic congestion is a result of number of private car use exceeding the road capacity. Park and ride facility is recognized as an effective way in reducing the number of private car use especially at the central part of the urban areas. It is accomplished by providing adequate parking spaces with affordable parking charges at the park and ride facility to induce the shift from private cars to public transportation. The purpose of this paper is to analyse the parking utilization pattern at the park and ride facility and the factors influencing the demand for the park and ride facility based on data from literature review. The analysis includes determining characteristics of the park and ride facility, demand for park and ride facility and factors affecting the parking demand at the park and ride facility.